IMPLEMENTASI METODE HYPNOTEACHING DALAM PEMBELAJARAN MENULIS TEKS INSPIRATIF BERORIENTASI PADA STRUKTUR DAN ASPEK KEBAHASAAN PADA PESERTA DIDIK KELAS IX DI SMPN 21 BANDUNG - Audrey Anastasya Bella (STKIP Subang, 2023)
The background of this research is that there are several problems that are often experienced by students when writing inspirational story texts, namely students often find it difficult to get ideas and develop them. This research uses quantitative methods. In research methodology, it is important to pay attention to research ethics and ensure that research is carried out with integrity and objectivity. The author shows excellent skills in planning learning to write inspirational story texts using the Hypnoteaching method. As for the research results: 1) The writer obtained a score of 3.79 for the assessment of lesson planning. This shows that the writer has a very good ability in planning learning. 2) Students demonstrate the ability to write inspirational story texts using the Hypnoteaching method. This can be confirmed through the results of the Wilcoxon signed rank test which was carried out on the pretest and posttest data from the experimental class and the control class. Based on the results of the test statistics, the experimental class obtained an asymp value. Sig. (2-tailed) of 0.000 <0.05, which indicates that the students' ability to write inspirational story texts using the Hypnoteaching method has increased. 3) the Hypnoteaching method for class IX students of SMPN 21 Bandung succeeded in improving student learning outcomes. The average value obtained by students in the experimental class who received the treatment of applying the Hypnoteaching method experienced a more significant increase compared to the average value obtained by students in the control class who did not receive the treatment of applying the Hypnoteaching method. This shows that the Hypnoteaching method is effective in improving students' learning outcomes in writing inspirational story texts.